Determining burn severity and its impact on post fire regeneration in the Nothofagus forests of Tierra del Fuego, Argentina. - Ruggirello, Matthew Joseph (2024)
In Tierra del Fuego, southern Argentina, recent wildfires in Nothofagus (southern beech) forests have produced post-fire conditions commonly associated with high burn severities (high mortality and deep ground-layer consumption). Still, burn severity has not been systematically categorized for fires in the region. In two recent wildfires (2008, 2019), we established 80 burned and 16 unburned (control) plots in N. pumilio and N. antarctica forests in which we visually estimated burn severity, measured live tree basal area, estimated bare-soil abundance, and tallied seedlings (≤30cm). Visual estimations classified 71% of post-fire plots as having burned at high severity (>90% overstory mortality, >50% bare-mineral soil) and 29% at low severity (≤90% but >0% overstory mortality, ≤50% bare-mineral soil but >0%). Average live basal area increased from 0 m2ha-1 in high-severity burn plots, to 5 m2ha-1 in low-severity plots, and 41 m2ha-1 in controls. Bare-soil dominated microsites represented 29% of all microsties in high-severity plots, 18% in low-severity plots, and 1% in controls. Seedling density was negatively correlated with both visual estimates of burn severity (r=-0.43, p<0.0001) and bare-ground abundance (r=-0.19, p=0.06), and was positively associated with live basal area (r=0.48, p<0.0001). Bare-soil thresholds for burn severity categories need to be adjusted based on our results and burn-severity classifications will be confirmed using remote-sensing and soil sample data. Still, studied wildfires were likely dominated by high-severity burn patches associated with low seedling densities. To maximize limited restoration resources, visual estimates of burn severity should be used to inform planting decisions. Areas with high mortality, dominated by bare-soil and low live tree basal area, should be prioritized in post-fire restoration efforts.